Augustine and manichaeism: new discoveries, new perspectives - Oort, Johannes van (Verbum et ecclesia, 2006)
The subject ‘Augustine and Manichaeism’ is a very extensive one. In this article the author confines himself to some main lines and argues that the subject is of central importance in the history of Christianity He shows how the theology of the most important Western Church Father was influenced by Manichaeism and suggests that without Manichaeism Western theology cannot really be comprehended.